2004
DOI: 10.1080/0269905031000149515
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial adjustment and employment outcome 2, 5 and 10 years after TBI

Abstract: Factors determining a poor prognosis for adaptation and re-insertion into the workplace are age, a low educational level, a lack of job qualifications and greater cognitive impairments. The significant differences found between the NRS-R of employed and unemployed patients suggest that this variable may be used to predict a subject's ability to return to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 12 publications
5
84
0
1
Order By: Relevance
“…Although no previous studies have used the GOSE to measure outcome at 10 years after injury, the rates of return to work and marital relationships compare favorably with those of other long-term TBI follow-up studies (Franulic et al, 2004;Hoofien et al, 2001;Koskinen, 1998;Tate et al, 2005;Thomsen, 1984Thomsen, , 1992Wood & Rutterford, 2006b). However, the lack of detail regarding rehabilitation received by these other groups and variability in injury severity across studies precludes direct comparison and comment on impact of rehabilitation on outcome.…”
Section: Discussionmentioning
confidence: 75%
“…Although no previous studies have used the GOSE to measure outcome at 10 years after injury, the rates of return to work and marital relationships compare favorably with those of other long-term TBI follow-up studies (Franulic et al, 2004;Hoofien et al, 2001;Koskinen, 1998;Tate et al, 2005;Thomsen, 1984Thomsen, , 1992Wood & Rutterford, 2006b). However, the lack of detail regarding rehabilitation received by these other groups and variability in injury severity across studies precludes direct comparison and comment on impact of rehabilitation on outcome.…”
Section: Discussionmentioning
confidence: 75%
“…It was also suggested that lower functional disability resulted from lower post-TBI psychological disturbance. Psychological adaptation may be the reason why the subjects in the extended injury group had adjusted to a new life after injury and felt more secure in terms of personal health and safety [Franulic et al 2004]. …”
Section: Pwimentioning
confidence: 99%
“…The physical and functional symptoms diminish during the first two post-trauma years, but the social and psychological difficulties tend to persist over time [2,3]. Current research has repeatedly demonstrated the importance of the cognitive, behavioural and emotional sequelae of TBI [4][5][6][7][8][9]. However, in the Sykes-Horn et al [10] study, only 5% of TBI patients have taken part in formal rehabilitation.…”
Section: Introductionmentioning
confidence: 97%